(untitled) (Conferencea, 2024)
The idea of goodness monism is the main idea of Shota Rustaveli’s philosophical outlook. Philosophical views given in his immortal poem " The knight in the panther’s skin.", his philosophical outlook, reflected in poetic and philosophical aphorisms, are noteworthy for us both from the artistic-aesthetic and ethical-philosophical point of view. Shota Rustaveli is first of all a genius poet and a great master of artistic words. However, he does not limit himself to artistic or religious representations, but devotes a lot of space to views of philosophical origin, the authors of which he himself names in the lines: "I like to learn from Plato." "When this matter is covered, the wise man will declare it." Mention of Plato and Dionysius Areopagel (Peter Iberi) in "The knight in the panther’s skin." is extremely important from the point of view of the origin of goodness, the monism of goodness. The most important idea among the three main ideas of Plato’s world of ideas is the idea of goodness. After Plato, his followers, who called themselves Platonists, at the end of ancient philosophy, based on the symphony of Plato and Aristotle, created a new original philosophical system called Neoplatonism. This theory was extremely popular in Georgia, especially in the form of the Neoplatonism of one of its main representatives, Procles Diadochos, on the basis of which the Areopagite-Christian theories of Dionysius Areopagel (Peter Iber) and then the Christian-Neoplatonist theories of Ioane Petritsi, which had a great influence at that time, were created . in the formation of the Renaissance humanism era of the world, as well as the Georgian thought and in particular the Georgian philosophical culture.